2015
DOI: 10.1007/s12070-015-0928-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Improvement of Nasal Symptoms Following Septoplasty with Partial Inferior Turbinectomy Versus Septoplasty Alone in Adults by NOSE Scale: A Prospective Study

Abstract: To compare the symptomatic improvement of nasal symptoms following septoplasty with partial inferior turbinectomy (groups A) versus septoplasty alone (groups B) and to assess the improvement of nasal symptoms in both surgical groups before and after surgery by NOSE scale. This Tertiary Hospital based study was carried out between August 2012 and April 2014. 60 cases with septal deviation and contralateral inferior turbinate hypertrophy. Nasal Obstruction Symptom Evaluation (NOSE) scale for evaluating nasal sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[18][19][20] Dinesh Kumar et al used the NOSE score for subjective evaluation, and they reported a 70-point NOSE score reduction after septoplasty and turbinoplasty in comparison with preoperative NOSE scores. 21 A pilot study was performed by Corredor-Rojas et al in 2017 in one of the institutions included in the present study. Similarly, in that study, nasal obstruction was measured through the NOSE and VAS scales and QoL through the GBI test, but just during a postoperative midterm period.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Dinesh Kumar et al used the NOSE score for subjective evaluation, and they reported a 70-point NOSE score reduction after septoplasty and turbinoplasty in comparison with preoperative NOSE scores. 21 A pilot study was performed by Corredor-Rojas et al in 2017 in one of the institutions included in the present study. Similarly, in that study, nasal obstruction was measured through the NOSE and VAS scales and QoL through the GBI test, but just during a postoperative midterm period.…”
Section: Discussionmentioning
confidence: 99%
“…Both septoplasty and turbinoplasty can be performed for patients with nasal congestion. For some severe cases, ear, nose, and throat (ENT) surgeons choose turbinoplasty with septoplasty [ 11 , 12 ]. ENT surgeons may adopt different approaches and surgical devices for septoplasty and turbinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that septoplasty with and without turbinoplasty successfully relieved nasal obstruction compared to baseline measurements. However, the symptomatic improvement was more pronounced in patients who underwent the combined procedure than in patients who underwent septoplasty alone [ 12 ]. Some studies have suggested that septoplasty with turbinoplasty reduces the chance of revision nasal surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the size of the septal body and turbinates can be calculated by measuring the area and determining their width. Thus, the shrinkage rate with postoperative measurements can be evaluated objectively in different tomographic planes 10–12 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the shrinkage rate with postoperative measurements can be evaluated objectively in different tomographic planes. [10][11][12]…”
Section: Surgical Techniquementioning
confidence: 99%